Punch-shear strength of three luting cements Evaluated at two differents periods - Freitas, Márcia Furtado Antunes de (2011)
Dental cements must present satisfactory  mechanical properties in order to support masticatory forces  and  occlusal  loads  in  the  oral  cavity.  The  punch shear strength is a simple and  efficient  method  to  evaluate the strength of a material, by means of an axial load applied to dislocate one or several materials. Thus, the objective of this work was to evaluate three dental cements (a zinc phosphate, a glass-ionomer, and a resin cement) as to their  punch  shear strength. For this test, specimens in a ring form matrix with dimensions of 14mm of internal diameter and 1.5mm of height were made, allowing for a disc of the materials with these dimensions to be obtained, which was placed in an adequate testing device. Ten specimens of each material were analyzed for the respective test at periods of 1 and 24 hours. The results were statistically evaluated with the two-way ANOVA test, followed by the comparative Tukey’s test (5%). The dental cement which obtained the highest values of punch shear strength was the resin cement, whereas the glass-ionomer cement obtained the lowest values among all the analyzed materials in both periods.